Socio-Psychological Features of Preschool Children with Unpopular Sociometric Statuses - Bodenova, Olga Viktorovna (Razvitie obrazovaniâ (Online), 2022)
The article presents the results of the study of some socio-psychological characteristics of preschool children with unpopular sociometric statuses. The sociometric structure of a small social group is the result of its development and has a significant impact both on the functioning of the group itself and on the socio-psychological development of its members. On the one hand, personality traits along with other factors of psychical development and socialization contribute to or hinder the acquisition of favorable sociometric statuses. On the other hand, the possession of a certain sociometric status has an impact on the development of socio-psychological characteristics of the individual. Children with unpopular statuses are situated at the zone risk. The aim of the work was to study the socio-psychological characteristics of children with unpopular sociometric statuses. The study was conducted in preschool educational institutions of Petrozavodsk, Prionezhsky and Medvezhyegorsky districts of the Republic of Karelia. We used some methods to test the hypothesis. These are the «Secret» method, «Observation of children's communication», the Rosenzweig test, the «Monitoring aggressive behavior of children» method. The results of the study. The study found that neglected and ignored children have got by aggression and anxiety; demonstration of aggression and anxiety in children with unpopular sociometric statuses are determined by the strength of the need for communication (initiative). These qualities are inherent in children who have a high need for communication. In rejected and isolated children with low need for communication, these qualities are not expressed. Anxiety differs in situations of interaction with peers or adults. The results of the study determine new tasks and the direction of correctional and developmental work with unpopular children.